(untitled) (SAARC Journal of Agriculture, 2020)
The cultivation of improved chickpea varieties has been increasing over time that kicks off the local varieties from the farmer’s field. Up-to-date socio-economic information regarding this issue is scanty in Bangladesh. That is why we analyze the profitability of improved chickpea variety and assess the impact of its cultivation on the livelihood of chickpea farmers in the high Barind region of Bangladesh. The values of benefit-cost ratio depict that the improved variety is more profitable in comparison to local chickpea variety; specifically, the benefit-cost ratio (BCR) of improved chickpea production is 1.87, while it is only 1.66 for local chickpea. To understand the wellbeing of chickpea farmers, the multidimensional livelihood index (MLI) following sustainable livelihood framework of the Department for International Development (DFID) is used, which constitutes the asset pentagon of five capitals namely human, physical, natural, financial and social capital. The MLI of improved and local chickpea growers are 0.51 and 0.39 respectively which belong in the middle livelihood category. Meanwhile, the MLI reflects that the improved variety cultivars are in a better livelihood condition than the local variety growers. Among all the five capitals of the MLI, the difference between these two groups is the largest in the case of social capital followed by financial capital. Since both groups have achieved far less MLI values than 1, the recommendation is therefore to ensure different types of facilities for the development of people of high Barind tract as well as increasing the production of improved chickpea. SAARC J. Agri., 18(1): 129-142 (2020)